The Effectivity of Multi Source Feedback (MSF) to Assess Professional Behaviour (Pb) of Nursing Students: An Evaluation Study - Asmara, Fatikhu Yatuni; Santoso, Agus (Nurse Media Journal of Nursing, 2015)
Background: Nurses are requested to give an excellent services to patients not only excellent in skills but also excellent in behaviour which serve comfort to patients. The behaviour is called professional behaviour or soft skill. Purpose: The aim of this research is investigating the effectiveness of MSF in assessing nursing students’ professional behaviour (PB).Methods: The design of the research is an evaluation study which compares the result of PB between before and after joining practice in clinical setting. The participants were thirty three participants consisting of 33 nursing students and 3 mentors. Data were collected using a quantitative approach. The participants are requested to do self and peer assessment using SPRAT modification form while mentors are asked to assess nursing students using the same form. The assessment was conducted twice, before and after joining internship. The data were analysed to compare the score of PB before and after joining the internship among group of participant using Paired sample T-test or dependent sample T test. Result: The results showed that there were differences of score between before and after joining internship with α = 0.000; 0.001; and 0.000 for self, peer, and mentor assessment respectively. There was no difference of score before joining internship among assessors with α = 0.509, and there was a difference of score after joining internship among assessors with α = 0.005. It means that MSF is an effective method to assess PB of nursing students. Conclusion: Applying MSF method to assess PB of nursing student is suggested for better assessment.